Pengaruh Motivasi Kerja, Gaya Kepemimpinan, Komitmen Kerja, dan Kerja Sama Tim terhadap Kinerja Pegawai pada Ditpam BP Batam - Mefri Yudi Wisra; Muhammad Rahmat; Syarifuddin Syarifuddin; Febdi Edward; Rahmad Budi Harto (Jurnal Riset dan Inovasi Manajemen, 2026)
This study examines the influence of Work Motivation, Leadership Style, Work Commitment, and Teamwork on the Work Performance of employees at the Directorate of Security (Ditpam) of the Batam Business Agency (BP Batam). A quantitative approach with an associative research design was employed. The population consisted of all Ditpam BP Batam employees, totaling 94 respondents, selected using a purposive sampling technique. Data were collected through questionnaires that had been tested for validity and reliability. The collected data were analyzed using multiple linear regression, along with simultaneous testing (F-test) and partial testing (t-test). The results indicate that simultaneously, Work Motivation, Leadership Style, Work Commitment, and Teamwork have a significant effect on employee Work Performance, as shown by an F-count of 12.455, which exceeds the F-table value of 2.47, and a significance value of 0.001 (< 0.05). Partially, each independent variable also demonstrated a significant influence on work performance, with t-count values exceeding the critical t-table value. These findings suggest that higher motivation, effective leadership, strong work commitment, and solid teamwork play an important role in improving employee performance. Therefore, it is recommended that the management of the BP Batam Security Directorate continuously enhance employee motivation, apply participatory leadership practices, strengthen organizational commitment, and foster harmonious teamwork to improve overall work performance.